A BACTERIOLOGICAL STUDY OF THE NATURAL FLORA OF EDIBLE OYSTER, CRASSOSTREA MADRASENSIS - DURAIRAJ, S; CHINNASAMY, G (Fishery Technology, 2017)
The total viable bacterial populations in the oysters and the sea water from the edible oyster farm at Tuticorin were Â· in the range of 103 to 104 per ml and 102 to 103 per ml respectively. The maximum most probable number of faecal coliform recorded during the one year period of study of both the oysters and seawater were 33 per 100 ml. Pathogenic bacteia (Salmonella sp., Vibrio cholerae, coagulase positive staphylococci and faecal streptococci were absent in oysters and farm water. Study of 197 (98 taken from oyster liquid and 99 from oyster farm water) randomly isolated cultures indicated that gram negative asporogenus rod-like bacteria of the Vibrio, Flavobacterium, Achromobacter and Pseudomonas gcoups were the dominant flora of the oyster liquid as well as seawater